Uniões homossexuais e possibilidades de analogia com uniões estáveis - Soares da Costa, Wellington (Nómadas. Critical Journal of Social and Juridical Science, 2009)
The objective of this study is to examine the legal possibilities of analogy stable homosexual unions with heterosexual unions stable legislated by Law No. 9278/1996 and the new Civil Code. Because it is not guided by statistics, but the interpretation of Brazilian law, the present research is qualitative and it used two technical procedures: literature search and information retrieval. The conclusion is that this analogy is possible and necessary, considering the constitutional principles of human dignity and equality, as well as the doctrinal definition and provision of legal institute of clogging of the law.